Metastatic Malignant Cutaneous Melanoma - Suárez, Hamiel; Mernies, Germán (Cirugía del Uruguay, 2020)
Presented at session 11th June 1937, with the contribution of Carlos M. Domínguez, Relator Carlos Stajano